PENINGKATAN PERILAKU SOPAN SANTUN MELALUI METODE BERCERITA PADA ANAK USIA 5-6 TAHUN DI TK LKIA II PONTIANAK SELATAN - Beata Sagala, Hana Martica (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThis study aims to improve the behavior of courtesy through the method of telling the story of children aged 5-6 years in TK LKIA II South Pontianak. The form of this research is classroom action research with descriptive method. Research subjects were teachers amounting to 1 person and 15 children. Based on the results of research that has been done and through the results obtained after the analysis of data that 1) learning planning in improving the behavior of courtesy through the method of storytelling in children aged 5-6 years can be categorized